To correctly demonstrate polynomial addition, we need to add the like terms of the two polynomials. Let's break down the expression:
Given:
\((2x^2 + 6x + 1) + (3x^2 + 3x + 9)\)
Now, we can add the like terms:
- The \(x^2\) terms: \(2x^2 + 3x^2 = 5x^2\)
- The \(x\) terms: \(6x + 3x = 9x\)
- The constant terms: \(1 + 9 = 10\)
Putting it all together, we get:
\(5x^2 + 9x + 10\)
Now, let's analyze the options given:
- \( (2x^2 + 6x + 1) + (3x^2 + 3x + 9) = 13x^2 + 9x + 10 \) (Incorrect)
- \( (2x^2 + 6x + 1) + (3x^2 + 3x + 9) = -x^2 + 3x - 8 \) (Incorrect)
- \( (2x^2 + 6x + 1) + (3x^2 + 3x + 9) = 5x^2 + 9x + 10 \) (Correct)
- \( (2x^2 + 6x + 1) + (3x^2 + 3x + 9) = 5x^4 + 9x^2 + 10 \) (Incorrect)
The correct option is:
(2x^2 + 6x + 1) + (3x^2 + 3x + 9) = 5x^2 + 9x + 10